Bacterial nanocellulose enhances osteogenic activity of Vat-based 3D-bio-printed silk fibroin hydrogels - Waidi, Yusuf Olatunji; Jagtap, Ashish; Dastagar, Syed G.; Chatterjee, Kaushik (International Journal of Biological Macromolecules, 2025)
Tissue engineering, particularly leveraging three-dimensional (3D) bioprinting, is emerging as a transformative solution to repair critical-size bone defects. However, identifying suitable biomaterials remains a key technological bottleneck in the field. Toward this broader goal, this study explored a composite bioink containing photocurable silk fibroin (SF) and bacterial nanocellulose (BNC) for fabricating scaffolds for bone tissue engineering (BTE) by 3D bioprinting using digital light projection (DLP). We prepared scaffolds with 0, 0.25, and 0.75 wt% BNC and characterized their physicochemical properties (degradation, viscoelasticity, porosity, compressive strength). We assessed samples in simulated body fluid (SBF) after 14 days to evaluate biomineralization. Additionally, using MC3T3-E1 preosteoblast cells, we examined cell viability, metabolic activity, proliferation, and osteogenic potential through alkaline phosphatase (ALP), Alizarin Red S (ARS), von Kossa, hematoxylin and eosin (H&E), and Picrosirius Red assays. The optimized bioinks produced hydrogels with controlled degradation, tunable viscoelasticity, interconnected pores, and significantly improved compressive strength. Specifically, 10 % methacrylated-silk with 0.75 % BNC (Silk-MA/0.75BNC) showed superior mechanical properties compared to 10 % Silk-MA or 10 % Silk-MA with 0.25 % BNC (Silk-MA/0.25BNC). In vitro studies confirmed enhanced biomineralization with Silk-MA/0.75BNC, increased calcium deposits, and improved cell viability and metabolic activity with BNC incorporation. Hence, the 3D-bioprinted composite scaffolds were shown to effectively support cell proliferation, with the 0.75 % BNC bioink significantly stimulating osteogenic markers. These results underscore the potential of Silk-MA/BNC composite bioinks for advanced 3D bioprinting of BTE constructs.
Keywords: Additive manufacturing; bacterial nanocellulose; Bone repair; Methacrylated silk fibroin

Vat-based 3D-bioprinted scaffolds from photocurable bacterial levan for osteogenesis and immunomodulation - Waidi, Yusuf Olatunji; Wagh, Vasudev S.; Mishra, Shivangi; Jhunjhunwala, Siddharth; Dastager, Syed G.; Chatterjee, Kaushik (Biomacromolecules, 2025)
Emerging techniques of additive manufacturing, such as vat-based three-dimensional (3D) bioprinting, offer novel routes to prepare personalized scaffolds of complex geometries. However, there is a need to develop bioinks suitable for clinical translation. This study explored the potential of bacterial-sourced methacrylate levan (LeMA) as a bioink for the digital light processing (DLP) 3D bioprinting of bone tissue scaffolds. LeMA was successfully synthesized, characterized, and used to fabricate 3D-bioprinted scaffolds with excellent printability and physicochemical properties. In vitro studies demonstrated superior cytocompatibility of 15% w/v LeMA gels compared to 20% gels. 15% LeMA gels supported osteogenic differentiation , as evidenced by alkaline phosphatase activity and mineral deposition by MC3T3 pre-osteoblasts. Importantly, the LeMA hydrogels positively modulated the macrophage phenotype, promoting the expression of the anti-inflammatory marker CD206. These findings suggest that 3D-printed LeMA scaffolds can create a favorable microenvironment for bone regeneration, highlighting their potential for tissue repair and regeneration applications.